Kegaduhan Tetangga Dalam Perspektif Hadits Muttafaq ‘Alaih Dan Pasal 503 KUHP - Sanabila Khairil Ahya; Tajul Arifin (Badan Penerbit STIEPARI Press, 2024)
In Islam, neighborly manners are highly recommended, because neighborly harmony is one of the main pillars in building a harmonious and prosperous society. In fact, the Prophet SAW also made this as one of the signs of one's faith. But on the other hand, it is not uncommon to find neighbors who make noise at night and often make other neighbors around them feel uncomfortable and disturbed. In addition to violating neighborly manners, it also violates positive law in Indonesia. The Criminal Code is one of the positive laws that regulates neighborly life, which discusses the rights and obligations of neighbors and the actions of neighbors that violate the law. The discussion that will be discussed in this research, namely regarding the noise of neighbors seen in the perspective of one of the hadiths and articles in the Criminal Code. This is intended so that ordinary people are not ignorant of the importance of neighborly manners and introduce the applicable law related to the issue so that the community can maintain harmony in neighboring. Normative juridical is the method of approach that researchers use to examine this research with secondary materials available laws, books, and journals.